1987
DOI: 10.1126/science.2433769
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Self, Nonself Discrimination

Abstract: The ability of immunodominant peptides derived from several antigen systems to compete with each other for T cell activation was studied. Only peptides restricted by a given transplantation antigen are mutually competitive. There is a correlation between haplotype restriction, ability to bind to the appropriate transplantation antigen, and ability to inhibit activation of other T cells restricted by the same transplantation antigen. An exception was noted in that a peptide derived from an antigen, bacteriophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
99
1
2

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(107 citation statements)
references
References 33 publications
5
99
1
2
Order By: Relevance
“…Class II molecules have clearly been shown to present "processed" antigen or synthetic peptides to helper T cells (3)(4)(5). In contrast, only recently has work from several laboratories indicated that class I molecules may also bind synthetic peptides, thereby forming target structures that can be recognized by CTLs.…”
mentioning
confidence: 99%
“…Class II molecules have clearly been shown to present "processed" antigen or synthetic peptides to helper T cells (3)(4)(5). In contrast, only recently has work from several laboratories indicated that class I molecules may also bind synthetic peptides, thereby forming target structures that can be recognized by CTLs.…”
mentioning
confidence: 99%
“…Debe haber por lo tanto un reconocimiento preferencial de ciertas secuencias de péptidos. En efecto, los primeros resultados muestras que hay tres tipos de estructuras (no excluyentes entre ellas) que pueden estar a la base de este reconocimiento selectivo: 1) péptidos amfifíli-cos que tendrían una parte hidrófoba, que haría contacto con el CMH, y una parte hidrofílica hacia el exterior, que haría contacto con el TCR; 2) aminoáci-dos cargados positivamente o glicinas, seguidos de 2 residuos hidrófobos y después un residuo polar o una glicina, y 3) péptidos que presentarían una homología con los antígenos del CMH (25,26).…”
Section: Presentacion De Antigenounclassified
“…< Cet article est dédié à la mémoire de Jean-Gérard Guillet [4]. Ces constatations ont conduit à proposer un modèle : dans la cellule présentatrice, les peptides issus de tous les antigènes dégradés se fixent sur un même site de la molécule du CMH, et la présence de ce site polymorphique, assurant la liaison de peptides très variés, peut expliquer la sélection du soi dans le thymus et la restriction par le CMH [5]. Peu après, l'association physique entre divers peptides immunogènes et les molécules de classe I du CMH humain, le système HLA, a été démontrée dans l'U152 Inserm de Jean-Paul Lévy à l'hôpital Cochin [6,7].…”
unclassified